Yevhenii Petrovych Sidorik (1931–2016) (Experimental Oncology, 2016)
Professor Yevhenii Petrovych Sidorik, well-known scientist in the fields of biophysics and experimental oncology, double Laureate of the State Prize in Science and Technology, Laureate of O.O. Bohomolets Prize and R.E. Kavetsky Prize of the NAS of Ukraine died on the 86th year of his life.